Pelotas (re)vista: a Belle Époque da cidade através da mídia impressa - Marroni, Fabiane Villela (2008)
The Belle Époque was a period of political, economical, social and cultural changes. It begins in France by the end of the 19th century, informed by the ideals of the French Revolution. Change, progress and freedom were the central themes on a search after civility, in a modernity-discourse. Alterations in values and usages of the European bourgeoisie were quickly assimilated in Brazil, most if all in Rio de Janeiro. The southern town of Pelotas had straight ties to the imperial court in Rio for political and economical seasons and to Europe because of the frequent travels by the high class to the old continent. For this reason it ended up absorbing such values. Due to this circumstance a reformulation of the urban space took place modifying the way of life of a part of the population. This process can be traced in the print media of those times. It is for this reason and because of a considerable socio-cultural effervescence that this work aims to analyze the Pelotas way of life and its visibility through the local press. These were ideas of progress and civilization disclosed through the press and based on the Belle Époque. The object of the analysis is the magazine Illustração Pelotense , published between 1919 and 1925. This choice was made because of the range of coverage of the magazine which shows how much the readers were interested in it. Though the focus lies on Illustração Pelotense , an exploratory study was carried out on the local print media from the middle of the 19th century aiming to understand the transformation process of the town, which included the press. A world-view enounced through signs of an other one , in a euphoric period, in a discourse of modernity, in changes of societies` way of life. The press was the instrument that enlightened the town. As theoretical and methodological basis we used the theory of discursive semiotics, from the regimes of visibility of Eric Landowski (1992, 2002) and Ana Claudia de Oliveira (1997). The Belle Époque of Pelotas shows a quick assimilation of new elements in a town with roots in the countryside. In that period Pelotas transformed itself, adapting to the European style that was absorbed in Brazil. The town changed, the press changed. Ultimately, it changed in its own ways, in its way of life, in its identity, in the recreation of the European style, in a specific way brazilianed